Uji Praktikalitas Perancangan Sistem Informasi Praktik Kerja Industri Berbasis Web di SMK Dhuafa Padang - Rahmat Dani; Indra Wijaya; Yuliawati Yunus (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to evaluate the practicality of designing information systems for web-based industrial work practices at SMK Dhuafa Padang using the waterfall research development method with 31 research subjects. The results of the research show that the developed system is very practical to use and has been tested for its feasibility and superiority through field trials. The development steps undertaken include analysis and definition of requirements, system and software design, implementation and unit testing, system integration and testing, as well as operation and maintenance. Practicality evaluation as a whole shows that the system has a very good level of practicality, which is equal to 87.96%. Based on the research results, there are four recommendations for further researchers. First, conducting further studies on the development of information systems for web-based industrial work practices at other SMKs that have the same needs. Second, extend existing features to improve system performance and user experience. Third, integrating this system with other existing information systems at SMK Dhuafa Padang. Fourth, conducting research on the effect of using a web-based industrial work practice information system on learning outcomes and student performance at SMK. It is hoped that the results of this study can become a reference or reference for further researchers in developing an information system for web-based industrial work practices at SMK.